Optimization Management for Chili (Capsicum annum L.) Production in Agroforestry System with Coconut (Cocos Nucifera L.) on Local Protected Coastline Areas - Dina Ruslanjari; Priyono Suryanto; Taufan Alam (Indonesian Journal of Geography, 2020)
Bugel coastline areas have the potential for horticulture commodities development. This study's objectives were mapping protected Bugel coastline areas, land evaluation, and yield response of chili in an agroforestry system with coconut trees on Bugel coastline areas. The research was conducted during April-July, 2015, in Bugel coastline areas, Panjatan District, Kulonprogo Regency, Special Province of Yogyakarta. The first stage was the literature study and field mapping by BING satellite imagery. The second method was an actual and potential land evaluation using the FAO version, Sys criteria, and Sys limitation. The third method was using a randomized complete block design (RCBD) with three blocks as replications. The results showed that a local protected coastline area allowed for the agriculture and forestry crops is >200 meters from the furthest tide point. The actual and potential land evaluation in all agroforestry phases were not suitable and marginally suitable. The initial phase showed the highest fresh fruit weight by 100.30 grams/plant, compared with the intermediate and advanced phases by 88.13 grams/plant 71.54 grams/plant.